Analysis of Student's Spatial Ability in terms of Van Hiele's Thinking Stages in Problem Based Learning - Hairunnisah Tanjung; Bornok Sinaga; Abil Mansyur (BIRCU, 2021)
This study aims to analyze students 'spatial mathematical abilities in terms of Van Hiele's thinking stages in problem-based learning models, as well as to find out the number of difficult indicators of students' mathematical spatial abilities in terms of Van Hiele's thinking stages in problem-based learning models. Researchers are the main research instrument, data obtained through several previous studies or journals about research on students' spatial abilities in terms of van hiele's thinking stages in problem-based learning. This study uses the analysis technique of the Miles and Huberman model. Data analysis activities, namely data reduction, display data, and conclusion drawing/ verification. The subjects in this study were journal articles on the analysis of students' spatial abilities in terms of van hiele's thinking stages in problem-based learning. The object of this research is the provision of a problem-based learning process. Based on the results of the study, there are students with high spatial abilities who have exploratory thinking processes, methodical thinking, analogical thinking, abstract thinking, synthesis, serendipity, and recycling ideas, students with high spatial abilities also have high imagination, students with spatial abilities are having a process exploratory thinking, serendipity, analogical thinking, semi-abstract thinking, and recycling of ideas and having moderate imagination, as well as students with low spatial abilities in understanding problems using exploratory, analogical, semi-abstract, synthesis thinking processes and have low imagery.